Dyeing assessment and antimicrobial activity of tetra azo acid dyes derived from 4,4'-(propane-2,2-diyl)bis(2-methyl-4,1phenylene) bis(3-aminobenzenesulfonate) - Patel, Snehal N.; Patel, Navin B. (IJRDO-Journal of Applied Science, 2016)
4,4'-(Propane-2,2-diyl)bis(2-methyl-4,1-phenylene)bis(3-aminobenzenesulfonate) wassynthesized by reduction of condense product of Bisphenol C and m-nitrobenzenesulfonylchloride. The compound was used as a bifunctional middle component in the preparation of tetraazo acid dyes. This di amino compound was tetra azotized and coupled with naphthalene basedacid coupling component to give various tetra azo acid dyes. The obtained dyes werecharacterized by spectroscopic technique (UV-vis., IR, NMR) and the dyeing assessment of alldyes was evaluated on wool, silk and nylon fabrics. These dyes gave brown, violet, yellow,orange and pink shades on each fibers with good to very good fastness properties. Thepercentage dye bath exhaustion, fixation and biological activity have also been studied.